Hush, hush - Fitzpatrick, Becca (New York : Simon & Schuster BFYR, 2009)
High school sophomore Nora has always been very cautious in her relationships, but when Patch, who has a dark side she can sense, enrolls at her school, she is mysteriously and strongly drawn to him, despite warnings from her best friend, the school counselor, and her own instincts.
014 up.
HL 640
Keywords: Supernatural -- Juvenile fiction; Angels -- Juvenile fiction; Dating (Social customs) -- Juvenile fiction; Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction